Flotation separation of coal dust from foundry dust enhanced by pre-soaking assisted mechanical stirring. (1st August 2023) - Gong, Xiaolong; Hu, Shengli; Liu, Xinwang; Yang, Mo; Jiang, Wenming; Fan, Zitian
Abstract: Foundry dust is the main refractory solid waste in the foundry industry, and its resource utilization is a top priority for realizing green and cleaner production. The massive amount of coal dust in foundry dust is a potential impediment to the recycling of foundry dust, and the efficient separation of coal dust is crucial to solving the above problems. In this paper, the flotation separation of coal dust from foundry dust enhanced by pre-soaking assisted mechanical stirring was reported. The influence of pre-soaking, stirring speed, and stirring time on the flotation results of foundry dust was systematically studied, and the enhancement mechanism was analyzed based on the microstructure and hydrophobicity of foundry dust. Flotation kinetics experiments with different stirring time were conducted to clarify the flotation process of foundry dust. The results indicate that the pre-soaking of foundry dust is beneficial for the water-absorbing swelling of clay minerals coated on the surface of coal dust, and the subsequent mechanical stirring pretreatment promotes the monomer dissociation of foundry dust, which increases the contact angle of foundry dust and considerably improves the flotation results. The optimal stirring speed and stirring time were 2400 rpm and 30 min, respectively. The classical first-order model presented the highest degree of fitting with the flotation data among the five flotation kinetics models. Therefore, the pre-soaking assisted mechanical stirring is a promising method for promoting flotation separation and the complete recycling of foundry dust. Highlights: The foundry dust consisted of clay minerals and coal dust, with a high LOI of 41.97%. A novel experimental method for recovering coal dust from foundry dust was developed. The influences of pre-soaking, stirring speed and stirring time on the flotation performance of foundry dust were investigated. Five flotation kinetics models were used to reveal the flotation process.